Resettler Input and Equity Outcomes in Climate-Related Resettlement in Iloilo, Philippines - See, Justin (Archīum Ateneo, 2023)
The World Commission of Dams (WCD) Framework was released in 2000 providing several recommendations to reduce the negative impacts of large dams. Those related to the resettlement of communities included improving livelihoods, resolving past injustices, and providing recourse mechanisms. However, the WCD Framework was not widely operationalised and the resettlement of communities remains a significant human rights issue. Recently, resettlement is being used to address a variety of issues such as environmental degradation, poverty, urbanisation, and climate change. It is estimated that millions of people will be required to move in response to climatic hazards in the coming decades. Early studies suggest that climate-related resettlements are set to reproduce the injustices documented in the WCD from decades of failed dam resettlements. To avoid a repeat of such failures, this chapter considers a climate-related resettlement project in Iloilo, Philippines, and asks: What lessons could have been learnt from the WCD Framework to improve its impacts? We attempt to answer this question by unpacking how the project (mis)aligns with WCD guidelines and analysing its implementation processes and socio-economic outcomes. We conclude by identifying which among the WCD guidelines might have been useful to avert the observed inequitable outcomes.